Conhecimento e uso de plantas medicinais nas comunidades de uma unidade de conservação: uma contribuição para a gestão da APA Algodoal-Maiandeua - MONTEIRO, Márcia Joana Souza (Universidade Federal do Pará, 2018)
This work aims at the proposal to contribute for the environmental management of Environmental Protection Area Algodoal-Maiandeua, by cultural record and appreciation of the local knowledge. This consideration is in order to provide systematic information on the uses and knowledge of medicinal plants for inclusion in the management plan and encourage sustainable use of natural resources by emphasizing the importance of recognizing these practices, as well as in official inclusion of medicinal plants for health care the local population and in the same direction for suggesting Policy of Medicinal Plants and Herbal Medicines (PNPMF) in such place. So, data collection focused qualitative methodology, because the quest for knowledge about man and his life was thus adopted a methodology informed by a theory about the very nature of man. Data collection emphasizes the qualitative methodology because the pursuit of knowledge about man and his life to take into account a certain methodology consistent with its nature. Moreover, several methods are adopted, with emphasis on observation and interview, the latter aiming to combine a degree of quantification from observation. As a tool was used semi-structured forms, applied by the Community Health Agents (CHA), activity implemented after training on ethnopharmacy and involving the active participation of communities. Literature searches were also performed in order to obtain the medicinal species already cataloged in previous surveys. The survey was conducted involving the four villages that form the APA Algodoal-Maiandeua (Algodoal, Camboinha, Fortalezinha and Mocooca). The answers lead to the achievement of objectives, providing information on medicinal plants and local knowledge related with them, and offering contributions regarding the management of conservation units for sustainable use.